Historical ecosystem models can serve as a baseline for indicator-based assessment: the North Sea - Saygu, İsmet and Thurstan, Ruth H. and Roberts, Callum and Heard, Zoe and Akoglu, Ekin and Halloran, Paul R. (Frontiers in Marine Science, 2025)
Knowledge of past ecosystems is essential to understand how marine ecosystems have changed under human pressure. This understanding is critical for the effective management of marine ecosystems today. However, there has been limited effort to investigate the historical state of marine ecosystems and their changes over time under human impact, particularly since the industrial revolution when fishing intensity markedly increased. In this study, we developed two mass-balanced Ecopath models with identical topology to create comparable representations of marine ecosystems of the North Sea in the 1890s and 1990s based on historical landings data of marine fisheries statistics from the ‘Fishery Board for Scotland’. While the 1890s represent the onset of industrial fisheries, the 1990s were specifically selected as a more recent reference point to align with existing models that are currently integral to ecosystem-based management in the North Sea. Indicator-based assessments revealed that direct and indirect impacts of fisheries on the food web triggered cascading changes in trophic interactions and ultimately led to a decline in the ecosystem’s maturity and resilience over the century, reflecting the industrialization of the North Sea fisheries. Our results now suggest that present day model-based fisheries management practices in the North Sea are based on ecosystem structure and function that were already degraded. Therefore, we propose the potential use of historical ecosystem models representing quasi-pristine state of ecosystems as baselines or thresholds for indicator-based assessments. Finally, this study emphasizes the importance of unveiling historical fisheries records from dusty archives.